2016
DOI: 10.1557/jmr.2016.174
|View full text |Cite
|
Sign up to set email alerts
|

The effect of core–shell particles on the mechanical performance of epoxy resins modified with hyperbranched polymers

Abstract: A novel core-shell particle that consists of epoxide-terminated hyperbranched polymer (HBP) and silica nanoparticles was incorporated into an epoxy/hydroxyl-terminated HBP blend to fabricate a high-performance epoxy thermoset. The effect of the core-shell particle content on the mechanical properties of the epoxy thermosets was investigated in detail. Results from tensile, flexural, and impact tests are provided. The impact fracture surface was studied by field emission-scanning electron microscopy. The incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The HBP shell was grown on the silica surface by polycondensation of succinic anhydride and DEA, according to a modified method reported in the literature [21]. The previously synthesized silica NPs (1.4 g) were mixed with succinic anhydride (3.14 g) and the reaction was conducted under magnetic stirring, in a nitrogen atmosphere at 140 °C for 4 h. Then, DEA (2.74 mL) was added to the mixture under a nitrogen atmosphere at 120 °C for 4 h. Afterward, the system was vacuumed for 2 h and the crude product was dissolved in DMF and centrifuged for 10 min to remove pure hyperbranched poly-amide esters.…”
Section: Methodsmentioning
confidence: 99%
“…The HBP shell was grown on the silica surface by polycondensation of succinic anhydride and DEA, according to a modified method reported in the literature [21]. The previously synthesized silica NPs (1.4 g) were mixed with succinic anhydride (3.14 g) and the reaction was conducted under magnetic stirring, in a nitrogen atmosphere at 140 °C for 4 h. Then, DEA (2.74 mL) was added to the mixture under a nitrogen atmosphere at 120 °C for 4 h. Afterward, the system was vacuumed for 2 h and the crude product was dissolved in DMF and centrifuged for 10 min to remove pure hyperbranched poly-amide esters.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 These hybrids can combine the advantages of core particles and organic polymers. 16 Gao et al. showed that SiO 2 nanoparticles grafted by rubbery block copolymer increased the ductility, fracture toughness and fatigue crack growth resistance of the epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%